2020
DOI: 10.1371/journal.pone.0229381
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new-generation antidepressants assessed with the Montgomery-Asberg Depression Rating Scale, the gold standard clinician rating scale: A meta-analysis of randomised placebo-controlled trials

Abstract: BackgroundIt has been claimed that efficacy estimates based on the Hamilton Depression Rating-Scale (HDRS) underestimate antidepressants true treatment effects due to the instrument's poor psychometric properties. The aim of this study is to compare efficacy estimates based on the HDRS with the gold standard procedure, the Montgomery-Asberg Depression Rating-Scale (MADRS). Methods and findingsWe conducted a meta-analysis based on the comprehensive dataset of acute antidepressant trials provided by Cipriani et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 35 publications
(47 reference statements)
4
14
0
2
Order By: Relevance
“…In accordance with previous re-analyses of the Cipriani dataset, all placebos were less effective than antidepressants (95% credible intervals [CrIs] excluding zero) [1,3,4], in line with the main results reported by Cipriani and colleagues [2].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with previous re-analyses of the Cipriani dataset, all placebos were less effective than antidepressants (95% credible intervals [CrIs] excluding zero) [1,3,4], in line with the main results reported by Cipriani and colleagues [2].…”
Section: Resultssupporting
confidence: 91%
“…The controversy about the clinical benefits of newgeneration antidepressants for the acute treatment of depression is ongoing and unresolved [1][2][3][4]. One major issue with antidepressant trials is that they exclusively rely on subjective outcomes, that is, clinician-ratings of depression symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Lorenzo-Luaces and colleagues’ [ 34 ] meta-analysis concluded comparable effectiveness of self-guided iCBT with that of antidepressants and in-person psychotherapy. In our trial, Thrive’s 8-week RCT between group (intervention vs control) effect size of 0.63 compared well with “mostly 8-week clinical trials of antidepressants for adults with unipolar major depression” between group (antidepressant vs placebo) effect sizes of 0.27 (Hamilton Depression Rating Scale) and 0.30 (Montgomery-Asberg Depression Rating Scale) in 109 antidepressant medication RCTs [ 35 ]. For longer-term outcomes, 12-month relapse rates from remission for Thrive at 8 weeks and STAR*D Phase I citalopram at 12 weeks [ 36 ] are 14.2% versus 33.5%, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…It has been repeatedly shown that antidepressants seem to reduce depressive symptoms with a statistically significant effect, but the effect sizes are small or minimal and without importance to patients [10,29,30]. A recent review of both within patient and between patient anchor-based approaches suggested that the minimal clinically important difference on the Hamilton Depression Rating Scale 17 (HDRS-17) is likely to be in the range from 3 to 5 points [31].…”
Section: Why Is It Important To Do This Review?mentioning
confidence: 99%